2012
DOI: 10.12693/aphyspola.121.254
|View full text |Cite
|
Sign up to set email alerts
|

The Smaller, the Better: From the Spider-Spinning to Bubble-Electrospinning

Abstract: Nanobubble dynamics in the spider-spinning procedure is elucidated, and a theoretical model is established to show why spider drag-line silk protein assemblies have extraordinary strength and toughness. Suggested by the spider-spinning, a bubble electrospinning is investigated for mass production of nanofibers within diameters 20 nm. El Naschie's E-infinity theory is a universal theory for nanotechnology. It is concluded that smaller is the way to have excellent thermal and electric conductivity, in fact the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The samples at the last 24 h of each test may not be diluted, and the data were processed through the standard curve of MB concentration and absorbance (Formula 2), multiplied by the corresponding dilution multiple, Calculate the concentration of MB at this time, as shown in Table 2. Calculate the change in adsorption rate according to the adsorption rate formula (1).…”
Section: Adsorption Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The samples at the last 24 h of each test may not be diluted, and the data were processed through the standard curve of MB concentration and absorbance (Formula 2), multiplied by the corresponding dilution multiple, Calculate the concentration of MB at this time, as shown in Table 2. Calculate the change in adsorption rate according to the adsorption rate formula (1).…”
Section: Adsorption Performance Analysismentioning
confidence: 99%
“…The spider spinning process is extremely captivating for many scientists, because the properties of the spider silk is inextricably linked with its spinning process. 1,2 The bubble electrospinning 3,4 was invented by inspiration of the spider spinning, and 3-D printing technology [5][6][7][8][9] can be optimized by spider's web design. It was reported that the spider spinning has the attractive property of minimal energy consumption, 2 the energy saving 10,11 and energy harvesting 12,13 are two key factors for a green earth.…”
Section: Introductionmentioning
confidence: 99%
“…The applied electrical field and coupling of surface charge result in a tangential stress on the bubbles by deforming them into a jet. [ 98 ] Conjugate electrospinning involves two high voltage supplies with opposite polarity with two different spinneret systems. This setup enables the simultaneous collection of two different polymers on the same collector that results in composite fibers with varied morphology.…”
Section: Electrospinningmentioning
confidence: 99%
“…Electronic, optical, electrical, and mechanical properties of such fibers can be easily modified [5,6]. Thus, nanofibers fabricated by electrospinning technique, have attracted considerable interest, to be used in many important applications, such as various sensors, solar cells, and photocatalytic devices [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%